Potential of Biomass Based Electricity Generation in Sri Lanka - KP Ariyadasa (Journal of Tropical Forestry and Environment, 2015)
Biomass has attracted much attention as a primary energy source for electricity generation due to its potential to supply low cost fuel source with considerable environmental and socio-economic benefits. Despite having favorable climatic conditions to grow and use biomass for electricity generation, biomass based electricity generation in Sri Lanka is lagging behind due to many reasons. Many countries rely on the agricultural or forestry by-products or residuals as the main source of biomass for electricity generation mainly due to the comparatively low cost and sustainable supply of these by-products. Sri Lanka does not have this advantage and has to rely mainly on purposely grown biomass for electricity generation. Development of short rotation energy plantations seems to be the best option available for Sri Lanka to produce biomass for commercial scale electricity generation. The highly favorable growing conditions, availability of promising tree species and a variety of plantation management options and significant environmental and socio-economic benefits associated with energy plantation development greatly favor this option. This paper examines the potential of using plantation grown biomass as a fuel source for electricity generation in Sri Lanka.